2007
DOI: 10.1002/cjoc.200790329
|View full text |Cite
|
Sign up to set email alerts
|

Excess Molar Volumes and Viscosities for Binary Mixtures of 1‐Alkoxypropan‐2‐ols with 1‐Butanol, and 2‐Butanol at 298.15 K and Atmospheric Pressure

Abstract: Excess molar volumes E m V and kinematic viscosities ν have been measured as a function of composition for binary mixtures of propylene glycol monomethyl ether (1-methoxy-2-propanol), MeOCH 2 CH(OH)Me, propylene glycol monoethyl ether (1-ethoxy-2-propanol), EtOCH 2 CH(OH)Me, propylene glycol monopropyl ether (1-propoxy-2-propanol), PrOCH 2 CH(OH)Me, propylene glycol monobutyl ether (1-butoxy-2-propanol), BuOCH 2 CH(OH)Me, and propylene glycol tert-butyl ether (1-tert-butoxy-2-propanol), t-BuOCH 2 CH(OH)Me with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…From the density data shown in Figure we calculated the excess molar volume V excess , defined by ρ = false( x 1 M 1 + x 2 M 2 false) false( x 1 V 1 + x 2 V 2 + V excess false) where ρ is the mixture experimental density, M i is the molar mass of i , and V i is the volume of 1 mol of substance i, which we calculated from the known densities of the pure components at 27 °C. The excess molar volume is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…From the density data shown in Figure we calculated the excess molar volume V excess , defined by ρ = false( x 1 M 1 + x 2 M 2 false) false( x 1 V 1 + x 2 V 2 + V excess false) where ρ is the mixture experimental density, M i is the molar mass of i , and V i is the volume of 1 mol of substance i, which we calculated from the known densities of the pure components at 27 °C. The excess molar volume is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…(a) Excess molar volume against mole fractions x 1 1-butoxy-2-propanol + x 2 1-hexanol (■); x 2 1-octanol (●); x 2 1-decanol (▲); 298.15 K. The smoothing of the curves have been drawn from eq . (b) Excess molar volume against mole fractions x 1 1-butoxy-2-propanol + x 2 1-methanol (■) Pal et al; x 2 1-ethanol (●) Ku et al; x 2 1-propanol (▲) Pal et al; x 2 1-butanol (▼) Pal et al; x 2 1-hexanol (⧫) Dubey et al; x 2 1-octanol (◀) Dubey et al; x 2 1-decanol (▶) Dubey et al; at 298.15 K. The smoothing of the curves has been drawn from eq .…”
Section: Resultsmentioning
confidence: 99%
“…As far we know there is no experimental data of densities and speeds of sound on a binary mixture of 1-butoxy-2-propanol with higher alcohols (1-hexanol, 1-octanol, and 1-decanol) that have been reported in the literature. Recently, several authors have studied the thermodynamic studies of the binary mixture of 1-butoxy-2-propanol with lower alcohols (ethanol, 1-butanol and 2-butanol). Therefore, it offers us a good opportunity to study the mixing behavior of 1-butoxy-2-propanol with higher alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the proportion of hydroxyl groups available for intermolecular hydrogen bonds in branched alcohols are different than normal alcohols in binary mixtures. Pal and Gaba[9,10] in their study found that the magnitude of excess molar volume of the binary mixtures of 1-tert-butoxy-2-propanol with 1-butanol is almost similar but for 2-butanol it shows a different behavior. This may be due to the different experimental techniques having been adopted for the measurement ofV m E .…”
mentioning
confidence: 92%
“…The binary mixtures of (alkoxyalkanols + alcohols) have been studied extensively and systematically in recent years. Recently, Pal and Gaba [8][9][10] have studied volumetric, acoustic and transport properties of the binary mixtures of 1-tertbutoxy-2-propanol, + 1-propanol, + 1-butanol and + 2-butanol at 298.15 K.…”
Section: Introductionmentioning
confidence: 99%